2001
DOI: 10.1099/0022-1317-82-1-129
|View full text |Cite
|
Sign up to set email alerts
|

T-helper and humoral responses to Puumala hantavirus nucleocapsid protein: identification of T-helper epitopes in a mouse model

Abstract: Puumala hantavirus (PUUV) is a rodent-borne agent causing nephropathia epidemica in humans, a milder form of haemorrhagic fever with renal syndrome occurring in Fennoscandia, central Europe and western Russia. In this study we characterized the immunogenicity of an E. coli-expressed nucleocapsid (N) protein of PUUV (strain Kazan-E6) in inbred mice (BALB/c, CBA and C57/BL6). The recombinant N (rN) protein raised PUUV-specific antibodies in all three tested murine haplotypes, and all IgG subclasses were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 49 publications
0
18
1
3
Order By: Relevance
“…In this manner, it is evident that antigenic peptides can dictate the quality of an immune response by virtue of their affinity for MHC molecules (52). Supporting this contention, de Carvalho Nicacio et al found MHC-specific differences in proliferation magnitude to recombinant Puumala virus N-Ag in inbred strains of laboratory house mice (48). In addition, some viral peptides are antagonistic to T cell responses, such that they can impact effector T cell maturation (53)(54)(55).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In this manner, it is evident that antigenic peptides can dictate the quality of an immune response by virtue of their affinity for MHC molecules (52). Supporting this contention, de Carvalho Nicacio et al found MHC-specific differences in proliferation magnitude to recombinant Puumala virus N-Ag in inbred strains of laboratory house mice (48). In addition, some viral peptides are antagonistic to T cell responses, such that they can impact effector T cell maturation (53)(54)(55).…”
Section: Discussionmentioning
confidence: 75%
“…The polyclonal T cell lines from acutely infected deer mice produced both type 1 and type 2 cytokines, including IFN-␥, IL-4, and IL-5, likely reflecting a polyclonal response and paralleling that of studies of house mice immunized with recombinant Puumala virus N-Ag (48). Absent in the response were the type 1 cytokines TNF and LT, suggesting that these cytokines have no or limited roles during deer mouse CD4 ϩ T cell responses to SNV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of disease generally correlates with the number of CTL (10,37,51). CTL epitopes were identified in all three viral structural proteins, whereas NP again seems to be the predominant immunogenic protein (62,63).…”
Section: Cytotoxic Cd8mentioning
confidence: 99%
“…Por otra parte, en un modelo murino en el que se administra la proteína N recombinante (Nr) del virus Puumala (PUUV, variedad de hantavirus de Europa), se encontró que el nivel de la respuesta humoral y celular estaba influenciada por el genotipo de los roedores, indicando que el haplotipo del huésped juega un papel importante en la respuesta inmune contra la proteína N de PUUV 25 .…”
unclassified